PENERAPAN MODEL PEMBELAJARAN COOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELASIII SDN 009 BINIO JAYA KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Elita Sukma; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : Observational action performing this was done bases its low usufruct acquired IPS studying student is brazed III. SDN 009 BinioJaya, this appears from startup data usufruct to study student with averagely which is 61,67. Student that reaches to assess corresponds to KKM (Minimum thoroughness criterion) of 30 students are as much 13 person (44,44%), meanwhile student that haven't reached KKM'S point as much 17 person (55,56%), specified KKM point which is 65. Base about problem that needs to be done by action research brazes with kooperatif's learning model Talking Stick's type. This research intent to increase IPS'S studying result III.class student SDN 009 BinioJaya on school year 2014 / 2015. This research is done in two cycles, where on each its cycle is done two times appointment gazes to show face and once daily dry run. After been performed its observational it, therefore gets to increase IPS'S studying result III. class student SDN 009 BinioJaya on Merchant activity material at environmentally home and schooled and money and utility material it. It can at see of percentage result data thoroughness studies individual and klasikal is student which is on percentages base score thoroughness 43,3% by average 61,67, worked up on i. cycle which is with thoroughness percentage 73,33% with average 68, worked up again on cycle II. which is with thoroughness percentage 93,33% by average 80. On activity learns and student also experience step-up on each its cycle. Activity learns on first cycle with percentage 83,33% worked up as 95,83% on second cycle. Student activity on first cycle with percentage 71,4% worked up as 91,05% on second cycle. Of acquired data gets to be known that learnings model Implement kooperatif Talking Stick's type on III.class student SDN 009 BinioJaya can increase student studying results.Key word: Kooperatif is Talking Stick's Type, IPS'S Learned result